FJSU: um framework para o desenvolvimento de jogos sérios ubíquos - Silveira Júnior, Garibaldi da (2019)
Nowadays, digital games end up exploiting the mobility potential of mobile devices, adding ubiquitous features such as connectivity to different types of sensors and different devices, and adapting content in real time without the player's perception of computational processes. games understood as ubiquitous games. Within this panorama, the ubiquitous serious games, which are those used in serious contexts such as education, health, training, tourism, etc., have emerged. The proposal of these games meets the need of the teachers to integrate the ubiquitous technologies in the teaching environment, however, it is perceived that they have difficulties in adapting to them, while they are already part of the daily life of the students. Based on this principle, it is necessary to have a tool, simple enough for education professionals, and digital game design students to be able to use it in the creation of serious games that are ubiquitous. This dissertation presents the creation of a gray box framework for the development of serious, ubiquitous games, called FJSU, which provides the developer with a structure that can be flexible and adapted to the content according to the game proposal, which is divided into two modules. the first one related to the development of the game, based on the Unity engine, called the application module, and the second responsible for storing user profile data, called the web module. The present research was developed in the Graduate Program in Educational Technologies in Network of the Federal University of Santa Maria, in the line of research of Development of Educational Technologies. As a result of the final evaluation, from the analysis of the questionnaires and videos recorded during this stage, it was observed that even with some limitations, the framework maintained satisfactory results in terms of its support of the game design student as a facilitator in the creation of serious games ubiquitous, however, it was perceived the need for specific assessments for the teachers public.